The UCLA Shoulder Score Is a Better Predictor of Treatment Success Than the Constant and Oxford Shoulder Scores After Arthroscopic Rotator Cuff Repair: A 2-Year Follow-Up Study - Vikaesh Moorthy, M.B.B.S.; Jerry Yongqiang Chen, M.B.B.S., M.R.C.S., M.Med., F.R.C.S., F.A.M.S.; Merrill Lee, M.B.B.S., M.R.C.S.; Benjamin Fu Hong Ang, M.B.B.S., M.R.C.S., M.Med., F.R.C.S., F.A.M.S.; Denny Tjiauw Tjoen Lie, M.B.B.S., F.R.C.S., F.A.M.S. (Arthroscopy, Sports Medicine, and Rehabilitation, 2021)
Purpose: The aim of this study was to determine the correlation between functional outcome scores and treatment success after arthroscopic rotator cuff repair. Methods: We conducted a retrospective cohort study of patients who underwent unilateral rotator cuff repair at a tertiary hospital between 2010 and 2015. University of California at Los Angeles Shoulder Score (UCLASS), Constant Shoulder Score (CSS), and Oxford Shoulder Score (OSS) were measured before and at 6, 12, and 24 months after surgery. Patients were divided into 2 groups at each follow-up: (1) those with successful treatment and (2) those with unsuccessful treatment. Treatment success was defined as simultaneous fulfilment of 3 criteria: clinically significant improvement in pain, expectations for surgery met, and patient satisfied with surgery. Results: A total of 214 subjects met the inclusion criteria. UCLASS was a consistent significant predictor of treatment success at 6 months (odds ratio [OR] 1.192, P = .005, 95% confidence interval [CI] 1.054-1.348), 12 months (OR 1.274, P < .001, 95% CI 1.153-1.406), and 24 months (OR 1.266, P < .001, 95% CI 1.162-1.380). Lower preoperative CSS was significant in predicting treatment success at 6 months (OR 0.952, P = .001, 95% CI 0.926-0.979), while larger tear size was significant in predicting treatment success at 24 months (OR 1.773, P = .043, 95% CI 1.019-3.083). Conclusion: UCLASS is a better tool for predicting treatment success than CSS and OSS in patients undergoing arthroscopic rotator cuff repair, up to a minimum of 24 months’ follow-up. A holistic assessment of shoulder function, taking into account both subjective and objective evaluation of function, as well as patient-reported satisfaction, is important in determining treatment success after arthroscopic rotator cuff repair. Level of Evidence: III, retrospective comparative study.